The Effect of Group Counseling Using the CBT Approach with Self-Control Techniques to Reduce TikTok Social Media Addiction - Rina Yulitri; Dasril Dasril; Fadhilah Syafwar; Sania Destia Putri; Desri Jumiarti; Afrizal Afrizal (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The development of social media has had a significant impact on adolescents' lives, one of which is addiction to using TikTok, which disrupts self-control, decreases productivity, and affects academic and social balance. This condition demands appropriate intervention strategies, one of which is through group counseling services based on Cognitive Behavior Therapy (CBT) with Self-Control techniques. This study aims to determine the effect of group counseling with a CBT approach using Self-Control techniques in reducing TikTok social media addiction among class X.E.1 students at SMAN 2 Lintau Buo. The research used a quantitative method with a one- group pretest-posttest experimental design. The research population was 32 students, with a purposive sample of 10 people. The instrument was a Likert-scale TikTok addiction scale consisting of 32 valid items. The analysis results showed a significant effect of group counseling services with self-control techniques on reducing TikTok addiction. The t-test value indicated the alternative hypothesis was accepted, while the N-gain test resulted in an average of 0.31, which falls into the medium category. Thus, group counseling with a CBT approach using self-control techniques is proven effective in reducing TikTok social media addiction among students. These findings provide practical implications for school counselors in designing interventions to help students manage social media use more healthily and productively. In addition, this study provides a theoretical contribution to the development of counseling research, particularly by enriching CBT-based and self-control intervention models for addressing digital media addiction among adolescents